Analisis Penilaian Kesehatan Pada Bank Umum di Indonesia - Hugo Prasetyo Winotoatmojo; Muhamad Risal Tawil; Diana Anggraini Kusumawati; Made Susilawati; Hartono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze and determine the health assessment of commercial banks in Indonesia. This study uses a qualitative approach with a literature study research design. This study uses a literature review type of various sources of reading articles, books, journals, and publications related to the health assessment of commercial banks, the legal basis of commercial banks, and RGEC. The findings in this study are that the health assessment of commercial banks is based on the Financial Services Authority Regulation (POJK) Number 4 / PJOK.03 / 2016 concerning the Health Assessment of Commercial Banks. Then the method used in the health assessment of commercial banks is the Risk-Based Bank Rating (RBBR) method, which includes Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC). The health assessment of commercial banks can also be classified into four levels of health, including PK-1 (Healthy / Very good), PK-2 (Quite Healthy / Good), PK-3 (Less Healthy), PK-4 (Unhealthy).